Philippine modern art and its critics - Coseteng, Alice M. L. (Unesco National Commission of the Philippines, 1972)
This anthology which represents a broad choice of articles, columns, and reviews on painting and sculpture published in the 1960s, is an attempt to underscore the cultural role of the art critics and the mass media, i.e., the press, in the Philippines. It hopes to put in perspective not only a decade of artistic activity but also the significance of that activity in the development of art in the country and in the cultural life of the people.